Response of wheat and chickpea cultivars to reduced levels of solar irradiance - U. MINA; S.D. SINGH; BHUPINDER SINGH; MUNMI KHAUND (Journal of Agrometeorology, 2015)
The study was carried out at the Indian Agricultural Research Institute, experimental fields (28° N, 77° E) during 2008-2009 and 2009-2010 rabi season to observe response of wheat and chickpea cultivars to reduced levels of solar irradiance. In the present study two wheat ( Triticum aestivum; HD 2643 and PBW 343) and two chickpea (Cicer arienitum L. ; BG 1105 and BGD 72) cultivars were subjected to 20 per cent and 35 per cent less levels of solar irradiance than the control that received 100 per cent natural sunlight during entire crop growth period. The results show that the height and leaf area index (LAI) of both the crops cultivars under reduced solar irradiance were more than natural light. Under reduced solar irradiance, height of wheat cultivar HD 2643 was more than PBW 343 and that of chickpea cultivar BG 1105 was more than BGD 72. Reduction in solar irradiance affected the photosynthesis and stomatal conductance process in both the crops. About 4-29 per cent reduction in rate of photosynthesis in wheat and chickpea varieties was observed under reduced levels of solar irradiance. Reduction in stomatal conductance under reduced levels of solar irradiance in wheat varieties was 6-28 per cent and in chickpea varieties it was 1-14 per cent. Biological yield of wheat and chickpea varieties was decreased by about 37-45 per cent and 13-53 per cent respectively, under reduced levels of solar irradiance. Observations show that among wheat cultivars PBW 343 was less affected by reduced levels of solar irradiance than HD 2643. Among chickpea cultivars BGD 72 was less affected by reduced levels of solar irradiance than BG 1105. The PBW 343 and BGD 72 cultivars of wheat and chickpea may be used by breeders to develop new varieties to increase agricultural production in climatic condition subjected to low irradiance.